LEVERAGING MODERN INNOVATIVE TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING (Neo Scientific Peer Reviewed Journal, 2023)
In the digital age, the incorporation of modern innovative technologies has become essential in the education sector, especially in the teaching of English as a second language. This experimental study investigates the impact of these technologies on language acquisition, retention, and overall engagement among students. By harnessing the power of adaptive learning platforms, artificial intelligence, virtual reality, and other cutting-edge tools, educators can enhance the efficacy and efficiency of English language teaching, ultimately promoting a more immersive and interactive learning environment for learners.